Economist on wall street : - Bernstein, Peter L. (Wiley, 2008)
Economist on Wall Street is a collection of writings from 1955 to 1970. The book is especially interesting because so many of Bernstein's observations reflect the most important issues of the present—the outlook for inflation and its control, the intricacies of monetary policy, the future of the dollar, and the dilemmas of household finances. Bernstein was also concerned with developments in portfolio management, including the new influence of institutional investors and rules for optimal asset mixes.